Konsep Tasawuf Ibnu Atha’illah al-Sakandari dan Relevansinya dengan Konseling Psikosufistik - Muhammad Taufiq Firdaus (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study is the branch of the big topic concerning Islamic counseling that is exclusively studied through Sufism approach. The Sufism concept of Ibn Athaillah in Kitab Al-Hikam is described in order to be an approach of Islamic counseling as the result of the harmonious combination between psychology and Sufism to actualize human mental health. The scope of this study is focused on the main problem namely how Sufism concept of Ibn Athaillah can be used as counseling approach. The method used in this study is literature review type qualitative approach. The primary data are collected from Kitab Al-Hikam by Ibn Athaillah As-Sakandari. The secondary data are collected from various supporting literatures concerning Sufistic counseling. Data are collected using documentation method. Then, the data are reduced and analyzed. The result of this study indicates that Sufism concept is always focused on heart and soul management in order to draw closer to Allah. This can be made to be one of approaches in Islamic counseling. Sufism concept of Ibn Athaillah stresses more on riyadhah al-qulub namely emphasis in the aspect of heart condition in guiding someone that wants to go to the path of goodness. The conclusion is that in conducting spiritual counseling, Sufism approach is relevant to be the basis and spiritual counseling method. Riyadhah al-qulub or emphasis on heart aspect is psychosufistic counseling based on Sufism concept of Ibn Athaillah As-Sakandari.